Evidence for Persistence of Sexual Evaluative Learning Effects. Issue 3 (13th January 2020) - Both, Stephanie; Brom, Mirte; Laan, Ellen; Everaerd, Walter; Spinhoven, Philip
Abstract: Introduction: Several studies demonstrated that genital arousal and enhanced positive affect toward neutral stimuli due to sexual conditioning did not extinguish during a brief extinction phase, but other studies showed contrasting results. Possible resistance to extinction of conditioned human sexual response has, however, not been studied using extensive extinction trials. Aim: To study resistance to extinction of conditioned sexual response in men and women. Methods: Healthy sexually functional men (N = 34) and women (N = 32) participated in a differential conditioning experiment, with neutral pictures as conditioned stimuli (CSs) and genital vibrostimulation as unconditioned stimulus. Only one CS (the CS+) was followed by the unconditioned stimulus during the acquisition phase. Main Outcome Measure: Penile circumference and vaginal pulse amplitude were assessed, and ratings of affective value and subjective sexual arousal were obtained. In addition, a stimulus response compatibility task was included to assess automatic approach and avoidance tendencies. Results: Men and women rated the CS+ as more positive than the CS− during all 24 extinction trials and demonstrated a slight tendency to approach the CS+ directly after the extinction procedure. Participants rated the CS+ as more sexually arousing than the CS− during 20 extinction trials. No evidence was found for conditioned genital sexual response. Clinical Implications: Learned sexual evaluations may be difficult to modify through an extinction procedure; therefore, unwanted but persistent subjective sexual evaluations may be better targeted by interventions such as the deployment of emotion regulation strategies. Strength & Limitations: Extensive extinction trials were used; however, only relatively short-term effects within one experimental session were studied and there was no (unpaired) control condition. Conclusion: The results provide evidence that conditioned sexual likes are relatively persistent, also at the behavioral level.